Congenital airway anomalies and syndromes associated in newborns with esophageal atresia - Claudia Norambuena; Patricio Varela; Yovanca Ramírez; Eduardo Leopold; Jorge Godoy; Alvaro Weibel (Elsevier, 2024)
Objective: This study aims to define the associated comorbidities, syndromes and anatomic findings in newborns with esophageal atresia using bronchoscopy. Method: Retrospective analysis of the database was performed on patients that underwent surgery with esophageal atresia or tracheoesophageal fistula diagnosis between 2016 and 2023 in Dr. Luis Calvo Mackenna Children´s Hospital in whom an airway study was done with rigid laryngotracheoscopy. Demographic data, comorbidities and airway anomalies were registered. Results: Data from 37 patients was analyzed. Comorbidities were present in 62.1 % of the patients. Airway anomalies such as tracheomalacia, laryngomalacia, tracheal diverticulum, congenital tracheal stenosis and cleft were present in 56.75 % of the patients. 72.9 % of the patients had Type C EA and in 32.4 % of the cases tracheoesophageal fistula was located at the carina. Conclusion: In the last 7 years we have done an airway study in 82.2 % of newborns with esophageal atresia. There is a high percentage of patients with airway anomalies, therefore we consider the importance of performing an endoscopic airway study in all patients with EA.